Patrimonio culturale e naturale della Campania rigenerazione urbana - Castagnaro, Alessandro; Aveta, Aldo (Fuori collana, 2023)
This volume brings together multiple contributions on an important topic such as regeneration in the Campania region. The Proceedings of the Conference, held on March 21, 2023, and sponsored by Rotary District 2101, testify to the association's important role in the community. At the center of the discussion is our region's cultural and natural heritage, whose territory is rich in resources, cultural assets, and landscape values but also very fragile. In the approaches to the future of this heritage, the theses of experts, academics, and representatives of local authorities - many members of Rotary Clubs in the District - are compared with methodological contributions, exemplifications, good practices, and proposals. The volume debates the contemporary challenges with new urban planning approaches for self-regenerating territories, with a new paradigm that sees historical cities as the engine for the territory's growth, including cultural development. At the center of the reflections are the architectural project, mobility as an essential factor for livability and quality of life, the management plan for the historic center of Naples Unesco, energy efficiency and seismic protection of the historic building, as well as new forms of experimentation of shared administration of heritage. Campania presents a vulnerable Apennine territory with severe abandonment phenomena of inland historical centers. That's the reason why it's necessary to adopt urgent and innovative solutions are needed, inspired by concepts of rebalancing, with the creation of networks and supra-municipal circuits of fruition. The construction supply chain is addressed by highlighting, on the one hand, the negative repercussions of an inadequate national policy on Building Bonuses and, on the other, the potential of a sector that represents an important engine of socioeconomic development projected toward digitalization and innovation. Concerning the Unesco heritage, the prospects are outlined valorization regarding the archaeological site of Pompeii and the historic center of Naples. Particular attention is paid to environmental protection: we refer to the effects of climate change, the defense of the coastal landscape, the sea resource, the burning problems of the recovery of Bagnoli, as well as the agricultural landscape and urban greenery. Therefore, a volume is particularly significant and of considerable interest for its extraordinary wealth of multidisciplinary content, scientific and popular relevance.